ADJUSTMENTS OF BOARD COMPOSITION DURING COVID-19 CRISIS: ANALYSIS OF THE MACEDONIAN COMPANIES - Eftimov, Lјupcho; Bozhinovska, Tihona (University of Zenica, Faculty of Economics, 2021)
The aim in this paper is to make an analysis of the reported changes in the boards’ composition of the Macedonian stock exchange listed companies during Covid 19 crisis. In order to achieve this objective, secondary data of the companies reports published on the Macedonian stock exchange website were used. The sample consists of 80 companies, and firstly we performed qualitative analysis on the companies’ reports regarding boards’ composition changes. Afterwards, in order to increase the understanding of the factors that determine boards’ composition in Macedonian joint-stock companies, we designed a model to examine the relation of company characteristics, industry characteristics and market perception of company value with board size, board independence and board diversity. The results from our analyses shows that during Covid 19 period substantial number of companies from the sample have made changes in board composition and only 9.38% of the companies that reported change decided to reappoint the same members. However, this does not mean that Covid 19 has been the only factor influencing the changes. Furthermore, one of our conclusions from the presented results in the study is that most of the variations in board/boards size can be explained by the differences in firm characteristics (in particular operating revenues and chosen boards structure), while the variations in board independence can be explained by firm characteristics (in particular operating revenues and chosen board structure) and industry characteristics.
Keywords: board composition, board size, board diversity, Covid-19 crisis, listed companies